2017
DOI: 10.31952/amha.15.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Rhazes, a pioneer in contribution to trials in medical practice

Abstract: Medicinska povijest pokazuje da su se perzijski liječnici služili znanstvenim metodama u liječenju, temeljenim na kliničkim iskustvima i promatranjima još od predislamskog vremena (prije 637. godine) i stoljećima poslije (u islamskom dobu). Rhazes je bio jedan od perzijskih liječnika priznat kao ljekarnik, kemičar i istaknuti znanstveni pisac o različitim temama iz medicine i filozofije. U ovom radu nastojali smo istražiti klinička iskustva, kao i etičke i kritičke stavove Rhazesa u medicinskoj praksi. Rhazes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…He had a great practical view and used his own research and experiences to develop pharmacy. Rhazes is known as a pioneer of animal and human studies to evaluate the efficacy and safety of his medicines and medical approaches (28). Fur- thermore, he had a critical perspective towards scientific issues and avoided accepting and copying predecessors' knowledge unless he would find them acceptable.…”
Section: Resale Daruhaye Cheshmi (Treatise Of Eye Medicines)mentioning
confidence: 99%
“…He had a great practical view and used his own research and experiences to develop pharmacy. Rhazes is known as a pioneer of animal and human studies to evaluate the efficacy and safety of his medicines and medical approaches (28). Fur- thermore, he had a critical perspective towards scientific issues and avoided accepting and copying predecessors' knowledge unless he would find them acceptable.…”
Section: Resale Daruhaye Cheshmi (Treatise Of Eye Medicines)mentioning
confidence: 99%
“…Interestingly, about 59% of Pharmacopoeia is obtained from herbal plants (Swerdlow, 2000). In the history, Persian Medicine (PM) dates back to 10,000 years ago which was one of the burgeoning schools of medicine (Ghaffari et al, 2014(Ghaffari et al, , 2017. PM with several thousands of manuscripts, famous scientists and verbal sources in different languages can be helpful in the treatment of various diseases and in the development of new drugs by using modern technology (Ahmadi et al, 2009;Goshtasebi et al, 2015;Pasalar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1 Traditional Persian Medicine (TPM) consists of huge practical experiences for disease prevention and treatment that have been used from more than 10,000 years. 8,9 It could be considered as a potential source for finding novel treatment strategies as shown in some recent researches. 10,11 In TPM, the emphasis is more on prevention rather than treatment.…”
mentioning
confidence: 99%
“…It has been used in TPM as an anti-inflammatory drug to relieve pain in multiple sclerosis. [8][9][10][11][12][13][14][15][16][17][18][19][20] It has been patented at the registration office of Islamic Republic of Iran (no: 29350) and classified as equivalent to food with no observable adverse effect level (NOAEL). 21 Our previous double blind, placebocontrolled, crossover study have shown that MS14 improve mobility and quality of life of patients.…”
mentioning
confidence: 99%